The relevance of governance models for estuary management plans - Fidélis, Teresa
The latest theories on the governance of water resources point to the need to adopt integrated approaches, allowing the mediation of conflict between public and private interests by building consensus to include the participation of stakeholders and civil society in formulating and implementing policies, thereby ensuring their legitimacy. Models of governance have particular relevance in the context of estuaries, because of the complexity associated with them. Estuaries are areas where valuable, highly sensitive and diverse natural systems coexist, which are frequently threatened by the numerous human activities concentrated there. They are also areas where several organizations overlap, with their own jurisdictions and management instruments and where there is a wide range of users with distinct interests. At a time when the Planos de Ordenamento de Estuários (POE) (Estuary Land Use and Management Plan), a new tool for water resource management and planning, are being drawn up in Portugal, this paper discusses the specificities of the new Portuguese estuary plans, as well as associated potentials and constraints to further understand how water resources and land use policies may effectively be integrated in estuary contexts. It critically analyses the Portuguese legal framework established for these plans, arguing that, in spite of the novelty of the newly defined legal measures to better plan and manage estuaries, implementation of its ambitious objectives requires a robust governance model for plan preparation and implementation. Taking into account the main institutional features of complex estuaries with various agencies, stakeholders and users, as well as relevant governance principles, this paper proposes a governance model capable of enriching the implementation of estuary plans by contributing to a stronger involvement of all stakeholders and users in the construction of the plan, allowing conciliation of interests and participation in decision-making, within a framework of collaborative governance. Whilst the paper focuses on the Portuguese Law, the approach adopted is also of interest to other countries to assessing estuary planning regulations and associated collaborative measures. © 2013 Elsevier Ltd. All rights reserved.